Cognitive abilities associated with the Silver-Russell syndrome. Issue 6 (December 1994) - Lai, K Y; Skuse, D; Stanhope, R; Hindmarsh, P
Abstract : There is no consensus opinion on whether or not cognitive impairments are found in the Silver-Russell syndrome. An investigation of a substantial sample was undertaken, using standardised assessments, in 20 boys and five girls aged 6.0 years to 11.8 years. Mean (SD) birth weights were -2.65 (0.95) SD scores, corrected for gestation. At evaluation the children had a mean (SD) age of 8.8 (1.8) years and a mean height of -2.26 (1.5) SD scores. Tests of cognitive abilities included assessments of general intelligence, reading and arithmetic attainments, and a cognitive processing task. Most had some degree of developmental delay: mean (SD) full scale IQ was 86 (24); 32% scored within the learning disability range (that is, IQ < 70); 40% were reading at least 24 months below their chronological age. Current head circumference correlated highly with full scale IQ. Assessments of special educational needs had been completed on 36%; 48% were receiving speech therapy. Approximately half of children with the Silver-Russell syndrome have significant impairment of their cognitive abilities.